Effect of Saturation State on Mudstone Mechanical Properties and the Fracture Zone Formation Around Mudstone Roadways - Jinghua Li; Guichen Li; Yuantian Sun; Fengzhen He; Haoran Hao; Sen Yang; Wei Li; Zhongwei Chen (Rock Mechanics and Rock Engineering, 2026)

Dynamic optimization of ship energy efficiency operational indicator based on self-Learning prediction model - Wenjie Guo; Guichen Zhang; Tie Li; Mengwei Chen (Ocean Engineering, 2026)

Water softening effect on the creep behavior of mineral components in red shale in Kaiyang phosphate mining area, China - Zhenqian Ma; Guichen Li; Lang Zhou; Yaodong Jiang; Changlun Sun (Bulletin of Engineering Geology and the Environment, 2026)

A Lightweight Image-Based Decision Support Model for Marine Cylinder Lubrication Based on CNN-ViT Fusion - Qiuyu Li; Guichen Zhang; Enrui Zhao (Journal of Marine Science and Engineering, 2025)
Under the context of “Energy Conservation and Emission Reduction,” low-sulfur fuel has become widely adopted in maritime operations, posing significant challenges to cylinder lubrication systems. Traditional oil injection strategies, heavily reliant on manual experience, suffer from instability and high costs. To address this, a lightweight image retrieval model for cylinder lubrication is proposed, leveraging deep learning and computer vision to support oiling decisions based on visual features. The model comprises three components: a backbone network, a feature enhancement module, and a similarity retrieval module. Specifically, EfficientNetB0 serves as the backbone for efficient feature extraction under low computational overhead. MobileViT Blocks are integrated to combine local feature perception of Convolutional Neural Networks (CNNs) with the global modeling capacity of Transformers. To further improve receptive field and multi-scale representation, Receptive Field Blocks (RFB) are introduced between the components. Additionally, the Convolutional Block Attention Module (CBAM) attention mechanism enhances focus on salient regions, improving feature discrimination. A high-quality image dataset was constructed using WINNING’s large bulk carriers under various sea conditions. The experimental results demonstrate that the EfficientNetB0 + RFB + MobileViT + CBAM model achieves excellent performance with minimal computational cost: 99.71% Precision, 99.69% Recall, and 99.70% F1-score—improvements of 11.81%, 15.36%, and 13.62%, respectively, over the baseline EfficientNetB0. With only a 0.3 GFLOP and 8.3 MB increase in model size, the approach balances accuracy and inference efficiency. The model also demonstrates good robustness and application stability in real-world ship testing, with potential for further adoption in the field of intelligent ship maintenance.

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Polymineralic Mudstone Exhibits Anisotropy due to the Preferential Orientation of Kaolinite Particles - Changlun Sun; Guichen Li; Zhenqian Ma; Jiahui Xu; Yuantian Sun (Rock Mechanics and Rock Engineering, 2025)

Impact of High-Concentration Biofuels on Cylinder Lubricating Oil Performance in Low-Speed Two-Stroke Marine Diesel Engines - Enrui Zhao; Guichen Zhang; Qiuyu Li; Saihao Zhu (Journal of Marine Science and Engineering, 2025)
With the implementation of the ISO 8217-2024 marine fuel standard, the use of high-concentration biofuels in ships has become viable. However, relatively few studies have been conducted on the effects of biofuels on cylinder lubrication performance in low-speed, two-stroke marine diesel engines. In this study, catering waste oil was blended with 180 cSt low-sulfur fuel oil (LSFO) to prepare biofuels with volume fractions of 24% (B24) and 50% (B50). These biofuels were evaluated in a MAN marine diesel engine under load conditions of 25%, 50%, 75%, and 90%. The experimental results showed that, at the same engine load, the use of B50 biofuel led to lower kinematic viscosity and oxidation degree of the cylinder residual oil, but higher total base number (TBN), nitration level, PQ index, and concentrations of wear elements (Fe, Cu, Cr, Mo). These results indicate that the wear of the cylinder liner–piston ring interface was more severe when using B50 biofuel than when using B24 biofuel. For the same type of fuel, as the engine load increased, the kinematic viscosity and TBN of the residual oil decreased, while the PQ index and the concentrations of Fe, Cu, Cr, and Mo increased, reflecting the aggravated wear severity. Ferrographic analysis further revealed that ferromagnetic wear particles in the oil mainly consisted of normal wear debris. When using B50 biodiesel, a small amount of fatigue wear particles were detected. These findings offer crucial insights for optimizing biofuel utilization and improving cylinder lubrication systems in marine engines.

Injectable self-healing alginate/PEG hydrogels cross-linked via thiol-Michael addition bonds for hemostasis and wound healing - Yuxuan Xie; Guichen Li; Jun Wu; Jiachen Zhu; Xuemei Cai; Peizuo Zhao; Dan Zhang; Yuan Zhong (Carbohydrate Polymers, 2025)

Topological rearrangement-derived edge-sharing [MO6] motifs on perovskite oxide for optimizing O-O bonding in water oxidation - Guichen Gao; Guangshe Li; Ming Ya; Nan Liu; Wei Shen; Pinxian Xi; Luyi Sun; Liping Li (Chemical Engineering Journal, 2024)

Comparing combined application of biochar and nitrogen fertilizer in paddy and upland soils: Processes, enhancement strategies, and agricultural implications - Xiaomai Yuan; Xiaoyan Gu; Run Liang; Guichen Ban; Li Ma; Tieguang He; Ziting Wang (Science of The Total Environment, 2024)

Integrated metabolomic and transcriptomic analysis of metabolic diversity and biosynthesis of glucosinolates and flavonoids in various cultivars of radish microgreens - Yuan Zhong; Yuxuan Xie; Dan Zhang; Guichen Li; Jihua Yu (Food Bioscience, 2024)

Rockburst intensity evaluation by a novel systematic and evolved approach: machine learning booster and application - Yuantian Sun; Guichen Li; Junfei Zhang; Jiandong Huang (Bulletin of Engineering Geology and the Environment, 2021)

Evaluation of Rockburst Hazard in Deep Coalmines with Large Protective Island Coal Pillars - Dong Li; Junfei Zhang; Yuantian Sun; Guichen Li (Natural Resources Research, 2021)

Endovascular treatment for aneurysms at the A1 segment of the anterior cerebral artery: current difficulties and solutions - Kun Hou; Guichen Li; Yunbao Guo; Jinlu Yu (Acta Neurologica Belgica, 2021)

Laboratory evaluation of shear strength properties for cement-based grouted coal mass - Yuantian Sun; Guichen Li; Hakan Basarir; Ali Karrech; Mohammad Reza Azadi (Arabian Journal of Geosciences, 2019)

The Arabidopsis nucleoporin NUP1 is essential for megasporogenesis and early stages of pollen development - Shuguang Bao; Guangshuang Shen; Guichen Li; Zhikang Liu; Muhammad Arif; Qingqing Wei; Shuzhen Men (Plant Cell Reports, 2019)